Prognostic significance of Ki67 and its correlation with mitotic index in dogs with diffuse large B-cell lymphoma treated with 19-week CHOP-based protocol - Sierra Matiz, Oscar R. [UNESP]; Santilli, Juliana; Anai, Leticia A. [UNESP]; Da Silva, Maria C. L. [UNESP]; Sueiro, Felipe A.; Sequeira, Júlio L. [UNESP]; Magalhães, Larissa F.; Magalhães, Geórgia M.; Tinucci Costa, Mirela [UNESP]; Calazans, Sabryna G. [UNESP] (SAGE Publications, 2018)
Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphoma in dogs. We evaluated Ki67 immunoexpression and mitotic index (MI) in dogs diagnosed with DLBCL and treated with a 19-wk CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) protocol. Twenty-nine lymph node samples from dogs diagnosed with DLBCL were analyzed for Ki67 immunostaining, and positive cells present in 1 cm2 were counted in a grid reticle for comparison of survival times above and below the means. The Ki67 mean was 107, and the MI mean was 21. There was a significant (p < 0.05) difference in median survival time between Ki67 immunostaining above and below the mean, with no difference in MI groups. Ki67 values >107 positive cells per 5 HPF counted in a grid reticle were associated with shorter survival times in dogs with DLBCL treated with a 19-wk CHOP-based protocol.
Keywords: Cell proliferation; dogs; immunohistochemistry; mitosis; prognosis